THE ANTIOXIDANT COMPOUNDS DETERMINATION OF VARIOUS BREWER'S SPENT GRAIN EXTRACTS - Marina V. Gernet; Maxim A. Zakharov; Irina N. Gribkova (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Brewer's spent grain is a brewing waste and contains a number of biologically active substances that not completely are extracted into malt wort during mashing, but are not use anywhere. The aim of the study was to obtain a comparative characterization of various surface active extractants, including cationic one, (benzyldimethyl-[3-(myristoylamino) propyl] ammonium chloride), in relation to phenolic compounds and amino acid content of brewer's spent grain, which can serve as the basis for the biologically active additives technology development. The extraction use made it possible to verify the soluble polyphenolic compounds (phenolic acids and rutin) and amino acids presence in the extracts. Studies have led to the conclusion that extractants can be presented in the following sequence in increasing extraction efficiency, i.e., in the strength of micelle formation, in increasing order: water, 0.01 % solution of benzyldimethyl-[3- (myristoylamino) propyl] ammonium chloride, 70 % solution of propane1,2-diol, 70 % solution of ethanol. All extracts are contained 18 amino acids, including 9 essential, 8 functional ones, and 5 polyphenolic substances, including rutin with P-vitamin activity. The carrying out alcohol extraction avoided the loss of essential amino acids by 4.5 % and functional ones - by 3.8 % respectively.